Advancing Endodormancy Release in Temperate Fruit Trees Using Agrochemical Treatments - Guillamón, Jesús Guillamón; Dicenta, Federico; Sánchez-Pérez, Raquel (Frontiers in Plant Science, 2022)
Endodormancy in temperate fruit trees like Prunus is a protector state that allows the trees to survive in the adverse conditions of autumn and winter. During this process, plants accumulate chill hours. Flower buds require a certain number of chill hours to release from endodormancy, known as chilling requirements. This step is crucial for proper flowering and fruit set, since incomplete fulfillment of the chilling requirements produces asynchronous flowering, resulting in low quality flowers and fruits. In recent decades, global warming has endangered this chill accumulation. Because of this fact, many agrochemicals have been used to promote endodormancy release. One of the first and most efficient agrochemicals used for this purpose was hydrogen cyanamide. The application of this agrochemical has been found to advance endodormancy release and synchronize flowering time, compressing the flowering period and increasing production in many species, including apple, grapevine, kiwi and peach. However, some studies have pointed to the toxicity of this agrochemical. Therefore, other nontoxic agrochemicals have been used in recent years. Among them, Erger® + Activ Erger® and Syncron® + NitroActive® have been the most popular alternatives. These two treatments have been shown to efficiently advance endodormancy release in most of the species in which they have been applied. In addition, other less popular agrochemicals have also been applied, but their efficiency is still unclear. In recent years, several studies have focused on the biochemical and genetic variation produced by these treatments, and significant variations have been observed in reactive oxygen species, abscisic acid (ABA) and gibberellin (GA) levels and in the genes responsible for their biosynthesis. Given the importance of this topic, future studies should focus on the discovery and development of new environmentally friendly agrochemicals for improving the modulation of endodormancy release and look more deeply into the effects of these treatments in plants.